The principles of CBLT and the development of key competencies - pcadmin, Kabulova Zulfiya Xojabaevna (Peerian Journals Publishing, 2025)
This article provides the application of Competency-Based Language Teaching (CBLT) in foreign language education, focusing on its role in fostering essential learner competencies for navigating a globalized world. Drawing on the principles of CBLT, which prioritize practical skills over rote learning, the study explores the development of three key competencies: value-semantic competence, which enables students to align language use with personal values and meaningful decision-making through interactive debates; learning and cognitive competence, cultivated via project-based learning to enhance independent intellectual skills, critical thinking, and information management; and cultural awareness competence, built through immersive cultural lessons that deepen intercultural understanding and communication. The findings underscore CBLT’s effectiveness in preparing learners for authentic communication and cultural engagement, offering a framework for educators to design dynamic, competency-driven foreign language curricula.
Keywords: CBLT; principles; skills